LDLR functional in vitro assays: a step forward for the correct genetic diagnosis of familial hypercholesterolemia - Azevedo, S. (2015)
Aim: Familial hypercholesterolaemia (FH) is an autosomal dominant disorder that confers an increased cardiovascular risk, due to high levels of cholesterol in blood since birth. FH has a prevalence of 1:500 and about 90% of these patients have mutations in the LDLR. Although more than 1600 alterations have been identified in FH patients, the majority of them remain without functional studies, being the aim of this work to construct vectors for the in vitro study of common alterations in Portuguese FH patients, contributing for phenotype/genotype clarification.